2016
DOI: 10.1111/ajad.12342
|View full text |Cite
|
Sign up to set email alerts
|

Degree of correspondence between daily monitoring and retrospective recall of alcohol use among men and women with comorbid AUD and PTSD

Abstract: Findings highlight the importance of considering the influence that moderating variables have on reporting of alcohol use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 29 publications
4
16
2
Order By: Relevance
“…Results suggest agreement between the retrospective TLFB and smartphone-based daily interviews when evaluating PDA and PHDD. This finding is in line with other recent research comparing technology-based assessment of daily drinking with Form-25 (Miller & Del Boca, 1994), another calendar-based retrospective recall measure in finding good correspondence between the two measurement methods for PHDD and PDA (Krenek, Lyons & Simpson, 2016). With regard to DDD, this study found significant disagreement between the two assessment methods over time, suggesting a deterioration of participants’ ability to recall the number of drinks consumed on a given drinking day with accuracy at more distal time points.…”
Section: Discussionsupporting
confidence: 91%
“…Results suggest agreement between the retrospective TLFB and smartphone-based daily interviews when evaluating PDA and PHDD. This finding is in line with other recent research comparing technology-based assessment of daily drinking with Form-25 (Miller & Del Boca, 1994), another calendar-based retrospective recall measure in finding good correspondence between the two measurement methods for PHDD and PDA (Krenek, Lyons & Simpson, 2016). With regard to DDD, this study found significant disagreement between the two assessment methods over time, suggesting a deterioration of participants’ ability to recall the number of drinks consumed on a given drinking day with accuracy at more distal time points.…”
Section: Discussionsupporting
confidence: 91%
“…Depression and treatment condition did not affect daily PTSD symptoms or moderate of the association of retrospective and daily PTSD. Men reported higher daily levels of re-experiencing and avoidance symptoms, and although Krenek et al, (2016) found that gender moderated correspondence of daily and retrospective drinking reports, we did not find similar effects for any symptom cluster. Age was significantly associated with daily avoidance and arousal symptoms, with older participants reporting higher daily levels of both symptoms, relative to younger participants.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, age may be associated with both retrospectively under- and over-reporting symptoms, therefore influencing concordance with daily reports. Conflicting evidence also exists regarding gender, with some research suggesting that women are more likely to retrospectively over-report emotion intensity (e.g., Feldman-Barrett, Robin, Pietromonaco, & Eyssell, 1998; Levine & Bluck, 1997), while other research has shown that men display worse agreement than women in their daily and retrospective reports of alcohol consumption (Krenek, Lyons, & Simpson, 2016). Another relevant participant characteristic is depression severity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data used in the current study have yielded previously published articles (Simpson, Stappenbeck, Luterek, Lehavot & Kaysen, 2014; Lehavot, Stappenbeck, Luterek, Kaysen & Simpson, 2015; Stappenbeck, Luterek, Kaysen, Rosenthal, Gurrad & Simpson, 2015; Browne, Wray, Stappenbeck, Krenek & Simpson, 2016; Krenek, Lyons & Simpson, 2016). …”
mentioning
confidence: 99%